Answer: Hence, the equation that could be used to find the number is given by
![(x)/(3)+(3x)/(4)-x=1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qbn35c96l7btiras2pbnkkvesb9pwswv1a.png)
Explanation:
Since we have given that
The sum of one-third of a number and three-fourths of the number exceeds that number by one.
So, the equation would be
![(x)/(3)+(3x)/(4)-x=1\\\\(4x+9x-12x)/(12)=1\\\\(13x-12x)/(12)=1\\\\(x)/(12)=1\\\\x=12](https://img.qammunity.org/2019/formulas/mathematics/middle-school/7u0b09o8ibnzvq81xrz3t4bqw4tl4scknm.png)
Hence, the equation that could be used to find the number is given by
![(x)/(3)+(3x)/(4)-x=1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/qbn35c96l7btiras2pbnkkvesb9pwswv1a.png)